2015
DOI: 10.1007/s11071-015-2142-x
|View full text |Cite
|
Sign up to set email alerts
|

A new image encryption scheme based on a simple first-order time-delay system with appropriate nonlinearity

Abstract: Nonlinear delay differential system (NDDS) is a family of hyperchaotic systems, which has attracted much attention in the last years, especially in optics. The NDDS is often modeled by a time delay that occurs between the signals at the input and the output, and a nonlinearity introduced by a function F. This paper introduces the Ikeda system that is considered system of infinite dimension and proposed an image encryption scheme by dynamic block. The encryption algorithm divides the image on dynamic blocks dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 22 publications
0
31
0
Order By: Relevance
“…Where when the entropy value closed to ideal value this mean it is difficult to retrieving the original image without knowing the key [26].…”
Section: Discussionmentioning
confidence: 99%
“…Where when the entropy value closed to ideal value this mean it is difficult to retrieving the original image without knowing the key [26].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we have focused on medical image encryption because of the heightened security concerns about patients' privacy and the need for a robust and secure encryption method for such images. Moreover, we found that various methods such as the approach of [41] are effective for the general image. The medical images mainly contain the few colors and low details.…”
Section: Medical Image Decryptionmentioning
confidence: 93%
“…Hence, these methods are not suitable for the medical image, and realizing the encryption take much time. Figure 2 shows the encryption result for medical image encryption by the method of [41]. Nonetheless, the proposed approach can be broadly implemented to other types of images.…”
Section: Medical Image Decryptionmentioning
confidence: 99%
“…To meet this challenge, a variety of encryption schemes have been proposed, (Chen et al 2004;Wang et al, 2016;Tang et al, 2016;Yang et al, 2010;Fu et al, 2011;Mannai et al, 2015;Chen et al, 2015;Zhao et al, 2015;Kanso & Ghebleh, 2015), recently there has been a growing interest in chaotic based image encryption, because they offer good properties in many concerned aspects regarding speed, security, computing power, complexity and computational overhead. The security of the cryptosystems based on chaotic stands on the used chaotic map and the adopted architecture, some chaotic based methods have security problems which are related to the small size of secret key and to the used chaotic map properties (Bechikh et al, 2015;Akhavan, 2015;Rhouma, 2008;Li, & Xuan, 2002).…”
Section: Introductionmentioning
confidence: 99%